Cover Picture: Supramolecular Self‐Assembly as a Tool To Preserve the Electronic Purity of Perylene Diimide Chromophores (Angew. Chem. Int. Ed. 12/2023). Issue 12 (15th February 2023) - Heckelmann, Ina; Lu, Zifei; Prentice, Joseph C. A.; Auras, Florian; Ronson, Tanya K.; Friend, Richard H.; Nitschke, Jonathan R.; Feldmann, Sascha
Abstract : A supramolecular chromophore cube based on perylene diimides (PDIs) is reported by Sascha Feldmann and co‐workers in their Research Article (e202216729 ). The rigid and shape‐persistent cage preserves the electronic purity of its PDI constituents and enables the observation of delayed fluorescence because of its bright excited multimer state, acting as an excitation reservoir. Self‐assembly can thus serve as a powerful tool for controlling electronic properties in molecular electronics devices.